Transformasi Pendidikan Pondok Pesantren Mauidzul Amin Al-Islamy Bunangkah Tengah : Memadukan Pendidikan Salaf dan Pendidikan Modern - Masrufah Masrufah (STIKes Ibnu Sina Ajibarang, 2025)
Mauidzul Amin Al-Islamy Islamic Boarding School is one of the Islamic Boarding School in Pamekasan that has undergone significant development in its educational system. This development includes integrating traditional salaf methods, such as the teaching of kitab kuning and Qur'an memorization (tahfidz), with modern education. This study aims to analyze the historical development of the pesantren, the curriculum system applied, and the impact of educational transformation on the quality of students (santri). The research employs a qualitative descriptive method with a historical and case study approach. Data were collected through interviews, direct observation, and relevant document analysis. The findings reveal that the educational transformation at Mauidzul Amin Al-Islamy has successfully improved the quality of the santri, both in their religious understanding and academic competencies. The students excel not only in Islamic scholarly traditions but also possess the skills to compete in the broader world. Flagship programs such as Qur'an memorization, mastery of foreign languages (Arabic, English, Mandarin, Spanish, Korean, and Japanese), and scientific activities like the Education Festival are the highlights of the pesantren.